Recursion and Equifinality in Relationship between Film and Theatre: Being John Malkovich - Getlík, Peter (Communication Today, 2018)
The essay focuses on the intersemiotic relationship of film and theatre that inevitably forces a metatextual dialogue of these semiotic systems in artworks. We have chosen the play-element of art to be the centre of our theorising, because we assume that it is often a significant interpretational key to the metatextual dialogue of multiple arts. These metatextual dialogues might be compared to ‘artistic games’. They mix multiple ‘artistic games’ and experiment with the combination of their principles and rules. They are metatextually explaining the rules of ‘artistic games’ during these experiments by revealing the hidden and hiding the obvious. They try to bend some rules and break some rules without spoiling the ‘game’. We observe the types of the play principle in these arts and then we describe behaviour of these semiotic systems through the opposition of recursion and equifinality. We extract models of the theatre fractal and the film net, verifying the legitimacy of this point of view via an analysis of the film Being John Malkovich.